2023
DOI: 10.3390/toxins15120688
|View full text |Cite
|
Sign up to set email alerts
|

A Hydrolase Produced by Rhodococcus erythropolis HQ Is Responsible for the Detoxification of Zearalenone

Junqiang Hu,
Shilong Du,
Han Qiu
et al.

Abstract: Zearalenone (ZEN), an estrogenic mycotoxin, is one of the prevalent contaminants found in food and feed, posing risks to human and animal health. In this study, we isolated a ZEN-degrading strain from soil and identified it as Rhodococcus erythropolis HQ. Analysis of degradation products clarified the mechanism by which R. erythropolis HQ degrades ZEN. The gene zenR responsible for degrading ZEN was identified from strain HQ, in which zenR is the key gene for R. erythropolis HQ to degrade ZEN, and its expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…was associated with archetypal salicylic acid and jasmonic acid defense pathways (Tan et al 2021). Hu et al 2023 also observed that R. erythropolis could also reduce zearalenone through the expression of the zenR gene (Hu et al 2023). According to McLeod et al 2006 the metabolic diversity of Rhodococcus species was also due to the presence and mobilization of large linear plasmids and multiple enzymatic homologs in catabolic pathways (McLeod et al 2006).…”
Section: Discussionmentioning
confidence: 96%
“…was associated with archetypal salicylic acid and jasmonic acid defense pathways (Tan et al 2021). Hu et al 2023 also observed that R. erythropolis could also reduce zearalenone through the expression of the zenR gene (Hu et al 2023). According to McLeod et al 2006 the metabolic diversity of Rhodococcus species was also due to the presence and mobilization of large linear plasmids and multiple enzymatic homologs in catabolic pathways (McLeod et al 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Given the substantial differences between field conditions and those used in in vitro studies, it is not unlikely that good degrading organisms in vitro would fail to deliver under field conditions. In spite of that, state-of-the-art research regarding the microbiological degradation of ZEN still often only focuses on the degradation in vitro [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. We want to emphasise the pivotal role of in planta validation in order to present strains that have a higher potential to be successful in a field application.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Risa et al studied the degradation and detoxification potential of 42 type strains of the genus Rhodococcus and concluded that one strain, namely R. percolatus JCM 10087 T , was able to degrade 95% of 1 mg/L ZEN and decreased oestrogenicity by 70% [39]. Lastly, Hu et al (2023) identified the key degradation enzyme ZenR that is responsible for the degradation of ZEN by R. erythropolis HQ [40]. All these studies were performed in vitro in liquid growth medium, which bears little resemblance to the plant environment in which ZEN is actually to be remediated.…”
Section: Introductionmentioning
confidence: 99%